Functional Ginger Extracts from Supercritical Fluid Carbon Dioxide Extraction via In Vitro and In Vivo Assays: Antioxidation, Antimicroorganism, and Mice Xenografts Models - Chih-Chen Lee; Li-Yu Chiou; Jheng-Yang Wang; Sin-You Chou; John Chi-Wei Lan; Tsi-Shu Huang; Kuo-Chuan Huang; Hui-Min Wang (The Scientific World Journal)
Supercritical fluid carbon dioxide extraction technology was developed to gain the active components from a Taiwan native plant, Zingiber officinale (ginger). We studied the biological effects of ginger extracts via multiple assays and demonstrated the biofunctions in each platform. Investigations of ginger extracts indicated antioxidative properties in dose-dependant manners on radical scavenging activities, reducing powers and metal chelating powers. We found that ginger extracts processed moderate scavenging values, middle metal chelating levels, and slight ferric reducing powers. The antibacterial susceptibility of ginger extracts on Staphylococcus aureus, Streptococcus sobrinus, S. mutans, and Escherichia coli was determined with the broth microdilution method technique. The ginger extracts had operative antimicroorganism potentials against both Gram-positive and Gram-negative bacteria. We further discovered the strong inhibitions of ginger extracts on lethal carcinogenic melanoma through in vivo xenograft model. To sum up, the data confirmed the possible applications as medical cosmetology agents, pharmaceutical antibiotics, and food supplements.